The cost of long term therapy for gastro-oesophageal reflux disease: a randomised trial comparing omeprazole and open antireflux surgery. Issue 4 (1st October 2001) - Myrvold, H E; Lundell, L; Miettinen, P; Pedersen, S A; Liedman, B; Hatlebakk, J; Julkunen, R; Levander, K; Lamm, M; Mattson, C; Carlsson, J; Ståhlhammar, N O; et al.
Abstract : BACKGROUND AND AIM: To comprehensively assess the relative merits of medical and surgical therapy for gastro-oesophageal reflux disease (GORD), health economic aspects have to be incorporated. We have studied the direct and indirect costs of medical and surgical therapy within the framework of a prospective randomised multicentre trial. METHODS: After initial treatment of reflux oesophagitis with omeprazole to control symptoms and to heal oesophagitis, 154 patients were randomised to continue treatment with omeprazole (20 or 40 mg daily) and 144 patients to have an open antireflux operation (ARS). In case of GORD relapse, patients allocated to omeprazole were offered ARS and those initially operated on had either a reoperation or were treated with omeprazole. The costs were assessed over five years from randomisation. RESULTS: Differences in cumulative direct medical costs per patient between the two therapeutic strategies diminished with time. However, five year direct medical costs per patient when given omeprazole were still significantly lower than for those having ARS in Denmark, Norway, and Sweden (differences were DKK 8703 (US1475), NOK 32 992 (US 5155), and SEK 13 036 (US 1946), respectively). However, in Finland the reverse was true (the difference in favour of ARS amounted to FMK 7354 (US 1599)). When indirect costs (loss of production due to GORD related sick leave) were also included, the cost of surgical treatment increased substantially and exceeded the cost of medical treatment in all countries. CONCLUSIONS: The total costs of medical therapy for chronic GORD were lower than those of open ARS when prospectively assessed over a five year period, although significant differences in cost estimates were revealed between countries.